Mathematical modeling of leptospirosis cases in Kuching incorporation with weather data - Aisyah, Mohammad (Universiti Malaysia Sarawak (UNIMAS), 2015)
Leptospirosis disease is among the world's common zoonosis that transmitted from the infected animals to the human. It is caused by pathogenic spirochetes of the genus Leptospira. Leptospirosis had been recognized as a re-emerging infectious disease among animals and humans. The infection works when the contaminated soil or water from the waste product of infected animal comes in contact to unhealed breaks such as skin or eyes. Several researchers have been reported that Leptospirosis disease works well with weather factor. Thus, in this final year project will be focusing on the relationship between the disease transmission with weather factor namely raining, humidity and surface air temperature. Correlation method is used to identify the relationship between disease transmission and weather factor. The result obtained from the correlation shows that there is a relationship between the disease transmission and the weather. In this project is also investigating the best mathematical function to represent for the transmission rate for each of the weather. Curve fitting method is used to find the best function. From the result, linear function is the best fit to represent the rainfall factor and cubic function is the best fit for surface air temperature factor and humidity.